Embedded thermocouple wall temperature measurement technique for scraped surface heat exchangers. (5th March 2017) - Martínez, D.S.; Illán, F.; Solano, J.P.; Viedma, A.
Highlights: Technique to retrieve the wall temperature in scraped surface heat exchangers. Embedded thermocouples, welding the thermocouple wires into the wall plate. 2D transient model: influence of thermocouple location and scraping velocity. Temperature oscillations due to the scrapers sweeping are damped through the wall. 1D steady model gives the time averaged heat transfer coef. in the scraped side. Abstract: Heating and cooling processes involving viscous fluids, crystallization processes or with fouling tendency require often the employment of scraped surface heat exchangers to enhance the heat transfer. In these cases, obtaining the heat transfer coefficient is complex due to the difficulty of measuring the wall temperature. The present work introduces an innovative measurement technique to retrieve the scraped wall temperature based on embedded thermocouples, welded directly into the wall plate. The thermocouple wires were introduced into a knockout and welded with a filler material. Once welded, the entire set was calibrated in a cold room at controlled temperature. A total of 26 T-type thermocouples were welded to a stainless steel wall substrate, tested later in a rotating scraped surface heat exchanger employed in the ice slurry production. The thermocouples presented a variance of 0.3 °C and an accuracy after calibration of 0.2 °C. The deviation between the scraped wall temperature and the thermocouple measurement was assessed by 2D numerical simulations of the transient heat conduction across the wall substrate. The influence of the wall substrate thickness, thermocouple location and scraping velocity has been considered.